PENGARUH SISTEM PENGENDALIAN INTERN PEMERINTAHAN (SPIP) TERHADAP KETERANDALAN LAPORAN KEUANGAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) PADA UPTP XXXIII CISEENG KABUPATEN BOGOR - Hutomo, Yoyok Priyo; Damayanti, D (JURNAL AKUNIDA, 2016)
The purpose of this study was determine the effect of the Government Internal Control System (SPIP) which refers to Regulation No. 60 of 2008 on the reliability of financial statements of the maagement of school operational funds (BOS). Tests conducted on 47 elementary and junior high schools in the region recipient BOS UPTP XXXIII Ciseeng District of Bogor. Collecting data using kuisiner instruments and analytical testing using IBM SPSS program version 22. The research method used in this research is quantitative deskriprif with the object used is 60 BOS is the principal manager and treasurer in District Ciseeng. From these results we can see the effect of simultaneously SPIP positive effect amounting to 86.3% while partial control environment, risk assessment, control activities and monitoring of information and communication positively influential to the reliability of financial statements BOS.Keywords: BOS, SPIP, Control Environment, risk assessment, control activities. And accounting information, and Monitoring.